MODERNITAS PENAFSIRAN AL-QUR’AN (Metodologi Tafsir Al-Munir Karya Wahbah Al-Zuhaili) - Wildan Hidayat (Cross-border, 2023)
The various problems contained in the interpretation of verses and which have given rise to debates among scholars have caught the attention of al-Zuhaili, however, his descriptions are not integrated with the discussion of verse interpretations. The contemporary or modern method used also combines two methods, namely tahlili (analytic) in explaining the linguistic and literary side of verses and a bit of mawdhû'i (thematic) impressions to explain a problem thoroughly, in order to obtain a comprehensive understanding of the message of the verses of al-Qur'an. -Qur'an, especially verses about stories of previous prophets and other major Islamic events. The modernity that appears in this interpretation marks a new path that can guide the people in the hegemony of the modernization of the times.